2005
DOI: 10.2106/jbjs.e.00251
|View full text |Cite
|
Sign up to set email alerts
|

Hypertrophy of Ligamentum Flavum in Lumbar Spinal Stenosis Associated with Increased Proteinase Inhibitor Concentration

Abstract: of ligamentum flavum in lumbar spinal stenosis associated with increased proteinase inhibitor concentration." The Journal of Bone and Joint Surgery.87,12. 2750-2757. (2005 Background: It is well known that age-related fibrosis, or decreases in the elastin-to-collagen ratio of the ligamentum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 30 publications
1
58
0
1
Order By: Relevance
“…Therefore, the correlation between LF thickness and LSCS symptoms could not be evaluated within the context of our study. In addition, LF thickening was defined by a thickness of ≥4 mm, representing a narrow range in comparison with previous studies [162526344243]. …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the correlation between LF thickness and LSCS symptoms could not be evaluated within the context of our study. In addition, LF thickening was defined by a thickness of ≥4 mm, representing a narrow range in comparison with previous studies [162526344243]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have suggested that increased concentrations of transforming growth factor-beta 1 (TGF-β1) or tissue inhibitors of metalloproteinases (TIMPs) might be associated with ligamentum flavum hypertrophy in patients with spinal stenosis 17-20). It is well known that MMPs can degrade elastin and collagen components within the various connective tissues of the body 6-8).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that the initial stage of hypertrophic LF is associated with different cytokines, including TGF-β and VEGF secreted by degenerated and herniated intervertebral disks and facet arthrosis [11]. With the progression of intervertebral space instability and chronic inflammation, a high degree of macrophage infiltration was identified as a major cellular source of various molecules [12], including matrix metalloproteases (MMPs) [13, 14], tissue inhibitors of matrix metalloproteases (TIMPs) [15, 16] during LF hypertrophy. The LF ECM can become disorganized and show decreased levels and degeneration of elastic fibers and increased levels of collagen fibers [17].…”
Section: Discussionmentioning
confidence: 99%